Composite material, preparation method and application thereof, and decorative product

By introducing specific copolymers and flame retardants into polycarbonate and combining the synergistic effects of other additives, the problem that traditional polycarbonate composite materials are difficult to have multiple excellent properties is solved, and the comprehensive performance improvement of composite materials is achieved, and strict flame retardant and anti-static requirements are met.

CN119684771APending Publication Date: 2025-03-25JIANGSU WOTE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411992356.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Traditional polycarbonate composite materials are difficult to combine excellent high impact, anti-static properties, ultraviolet resistance, flame retardant and environmentally friendly, and low odor characteristics, especially when meeting the national interior flame retardant requirements of the new version of the operating vehicle.

Method used

By introducing acrylonitrile-styrene-acrylate copolymer into the polycarbonate and combining the synergistic effects of composite flame retardant, polymer antistatic agent, compatibility agent, toughener, antioxidant and light absorber, the ratio of each preparation raw material is controlled to improve the flame retardant environmental protection and antistatic properties of the composite material while maintaining good mechanical properties.

Benefits of technology

It has achieved the excellent comprehensive mechanical properties, ultraviolet resistance, flame retardant and environmental protection and antistatic properties of composite materials, and can meet the requirements of decorative products for high mechanical properties, ultraviolet resistance, flame retardant and environmental protection and antistatic properties, and is suitable for electrical appliances, automobiles, aerospace, construction and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223916430000021
    Figure BDA0005223916430000021
  • Figure BDA0005223916430000022
    Figure BDA0005223916430000022
  • Figure BDA0005223916430000051
    Figure BDA0005223916430000051
Patent Text Reader

Abstract

The invention relates to a composite material, a preparation method and application thereof and a decorative product. The composite material comprises the following components in percentage by mass: 25%-60% of polycarbonate; 19%-60% of an acrylonitrile-styrene-acrylate copolymer; 2%-11% of a compatilizer; 2%-10% of a toughening agent; 5%-15% of a polymer antistatic agent; 1%-10% of a compound flame retardant; 0.3%-1% of an antioxidant; 0.3%-2% of a light absorber; wherein the weight ratio of the polycarbonate to the acrylonitrile-styrene-acrylate copolymer is (0.45-15): 1, and the weight ratio of the polycarbonate to the compound flame retardant is (3-10): 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer composite materials, and in particular to a composite material and a preparation method and application thereof, and a decorative product. Background Art

[0002] Polycarbonate PC has many advantages such as high heat resistance, high transparency, excellent mechanical properties and good flame retardancy, and is widely used in automotive materials and other industries. However, it also has obvious disadvantages, such as high sensitivity to notches, easy stress cracking, and high viscosity that is not conducive to processing. In order to better utilize its advantages and effectively improve its disadvantages, people have found that it is relatively easy to prepare alloy materials by blending and modifying with other resins. For example, the preparation of PC / ABS alloy can effectively improve its disadvantages of notch sensitivity and high viscosity. PC / ABS alloy has low viscosity, easy processing, good toughness and is widely used in automobiles and other industries, but it still has the problem of poor weather resistance.

[0003] Moreover, in modern industrial production and daily life, plastic products easily accumulate static electricity and attract dust. In severe cases, the hazards of static electricity may even cause major losses and disasters. The antistatic properties of plastic products are often improved through methods such as air ionization, metal contact discharge, conductive material introduction, surface hygroscopic film formation, and the application of antistatic agents. However, it is often difficult to take into account the excellent mechanical properties of plastic products.

[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention

[0005] Based on this, it is necessary to provide a composite material and its preparation method and application, and decorative products, which composite material not only has excellent comprehensive mechanical properties, but also has good anti-ultraviolet, flame retardant, environmental protection and antistatic properties.

[0006] This application is implemented through the following technical solutions:

[0007] In one aspect of the present application, a composite material is provided, wherein the composite material comprises the following components by mass percentage:

[0008]

[0009] The weight ratio of the polycarbonate to the acrylonitrile-styrene-acrylate copolymer is (0.45-15):1, and the weight ratio of the polycarbonate to the compound flame retardant is (3-10):1.

[0010] The above-mentioned composite material of the present application simultaneously introduces a compound flame retardant and a polymer antistatic agent into a system of polycarbonate and acrylonitrile-butadiene-styrene graft copolymer in a specific ratio, and cooperates with the synergistic effect of a compatibilizer, a toughening agent, an antioxidant and a light absorber. By controlling the specific ratio of each preparation raw material and the weight ratio of polycarbonate to the acrylonitrile-styrene-acrylate copolymer, the components work synergistically, so that after the addition of the compound flame retardant and the polymer antistatic agent, the flame retardant, environmental protection and antistatic properties of the composite material are increased while maintaining good mechanical properties, so that the composite material has excellent comprehensive mechanical properties, anti-ultraviolet properties, flame retardant, environmental protection and antistatic properties, so that it can meet the requirements of decorative products for high mechanical properties, anti-ultraviolet, flame retardant, environmental protection and antistatic properties.

[0011] In some embodiments, the composite material includes the following components by mass percentage:

[0012]

[0013] In some of the embodiments, the weight ratio of the polycarbonate to the acrylonitrile-styrene-acrylate copolymer is (2-5):1, and the weight ratio of the polycarbonate to the compound flame retardant is (5-8):1.

[0014] In some embodiments, the polycarbonate satisfies at least one of the following characteristics:

[0015] (1) The polycarbonate comprises bisphenol A type aromatic polycarbonate;

[0016] (2) The weight average molecular weight of the polycarbonate is 20,000 g / mol to 30,000 g / mol.

[0017] In some embodiments, the composite material satisfies at least one of the following characteristics:

[0018] (1) Based on the weight of the acrylonitrile-styrene-acrylate copolymer, the mass content of the acrylate structural unit is 35% to 85%;

[0019] (2) The compatibilizer includes styrene-N-phenylmaleimide-maleic anhydride copolymer;

[0020] (3) The toughening agent includes methyl methacrylate-butadiene-styrene copolymer.

[0021] In some embodiments, the composite flame retardant comprises magnesium hydroxide, zinc borate and an organophosphorus flame retardant;

[0022] Optionally, the mass ratio of the magnesium hydroxide, the zinc borate and the organophosphorus flame retardant in the composite flame retardant is (1.5-2.5):(2.5-3.5):(4.5-5.5).

[0023] In some embodiments, the composite material satisfies at least one of the following characteristics:

[0024] (1) The polymer antistatic agent comprises at least one of polyetheresteramide, polyetheramide and polyetherester;

[0025] (2) the antioxidant comprises at least one of a hindered phenol antioxidant and a phosphate antioxidant;

[0026] (3) The light absorber includes a benzotriazole light absorber.

[0027] Another aspect of the present application provides a method for preparing a composite material, comprising the following steps:

[0028] The components of the composite material are mixed and extruded.

[0029] The present application also provides the use of the above composite material in preparing decorative products.

[0030] Another aspect of the present application provides a decorative product, the decorative product comprising the composite material described above;

[0031] Optionally, the decorative article comprises an automotive interior trim part. DETAILED DESCRIPTION

[0032] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0033] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0034] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "one" before the elements or components of the present application are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "one" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number obviously refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0035] The weight of the relevant components mentioned in the specification of the examples of this application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the specification of the examples of this application, it is within the scope disclosed in the specification of the examples of this application. Specifically, the weight described in the specification of the examples of this application can be mass units known in the chemical industry such as μg, mg, g, and kg.

[0036] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0037] In traditional technology, the most commonly used method to prevent static electricity from being generated on the polymer surface is to use an antistatic agent, which is a chemical additive mainly composed of a surfactant that can prevent the accumulation of static electricity or effectively dissipate static electricity.

[0038] However, the technicians of the present application found that due to the poor chemical corrosion resistance of polycarbonate and the high processing temperature of 300°C, the antistatic agent will be decomposed during the process. Therefore, for polycarbonate and its composite materials, the method of using antistatic agents to improve the antistatic performance is generally to use the surface coating method, but it is often difficult to take into account the excellent mechanical properties of plastic products.

[0039] Furthermore, with the issuance of the new version of the national standard flame retardant requirements for commercial vehicle interiors JT / T 1095-2016, as shown in Table 1 below, the flame retardant requirements for interior materials of ordinary commercial vehicles have reached a new level. Compared with the old version of the flame retardant requirements, the requirements for smoke density and oxygen index have been added, and the technical standards are more stringent.

[0040] Table 1

[0041]

[0042] When a fire occurs, a large amount of toxic gas is the cause of secondary damage. Therefore, how to further improve the flame retardant properties of polycarbonate composite materials is one of the technical issues that urgently need to be solved. At the same time, with the enhancement of environmental awareness, the air quality inside passenger cars is also the focus of people's attention, especially for interior materials that are in close contact with drivers, and the emission requirements will become higher and higher. In summary, it is difficult for traditional polycarbonate composite materials to have excellent high impact resistance, antistatic performance, UV resistance, flame retardant and environmental protection, and low odor.

[0043] Therefore, the technical personnel of this application obtained the technical solution of this application based on their own many years of research and development and actual production experience in this field and after a large number of creative experiments.

[0044] An embodiment of the present application provides a composite material, which includes the following components by mass percentage:

[0045]

[0046] The weight ratio of the polycarbonate to the acrylonitrile-styrene-acrylate copolymer is (0.45-15):1, and the weight ratio of the polycarbonate to the compound flame retardant is (3-10):1.

[0047] The above-mentioned composite material of the present application simultaneously introduces a compound flame retardant and a polymer antistatic agent into a system of polycarbonate and acrylonitrile-butadiene-styrene graft copolymer in a specific ratio, and cooperates with the synergistic effect of a compatibilizer, a toughening agent, an antioxidant and a light absorber. By controlling the specific ratio of each preparation raw material and the weight ratio of polycarbonate to acrylonitrile-styrene-acrylate copolymer, the components work synergistically, so that after the addition of the compound flame retardant and the polymer antistatic agent, the flame retardant, environmental protection and antistatic properties of the composite material are increased while maintaining good mechanical properties, so that the composite material has excellent comprehensive mechanical properties, UV resistance, flame retardant, environmental protection and antistatic properties, so that it can meet the requirements of decorative products for high mechanical properties, UV resistance, flame retardant, environmental protection and antistatic properties.

[0048] Therefore, the composite material of the present application can be widely used in the fields of electrical appliances, automobiles, aerospace, construction, etc.

[0049] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0050] It should be noted that the polycarbonate "25% to 60%" can take a numerical range of 25% to 60%, which is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. For example, it includes but is not limited to: 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59% or 60%; or a range consisting of any two of these values, as an example, including: 30% to 60%.

[0051] The acrylonitrile-styrene-acrylate copolymer "19% to 60%" can take a numerical range of 19% to 60%, and this range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. For example, including but not limited to: 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59% or 60%; or a range composed of any two of these values, as an example, including: 25% to 60%.

[0052] The compatibilizer "2% to 11%" can take a numerical range of 2% to 11%, which is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. For example, it includes but is not limited to: 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or 11%; or a range consisting of any two of these values, as an example, including: 3% to 10%.

[0053] The toughening agent "2% to 10%" can be taken as a numerical range of 2% to 10%, and the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. For example, it includes but is not limited to: 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; or a range consisting of any two of these values, as an example, including: 2% to 9%.

[0054] The polymer antistatic agent "5% to 15%" can take a numerical range of 5% to 15%, which is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. For example, it includes but is not limited to: 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%; or a range consisting of any two of these values, as an example, including: 5% to 12%.

[0055] The compound flame retardant "1% to 10%" can take a numerical range of 1% to 10%, and the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. For example, it includes but is not limited to: 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; or a range consisting of any two of these values, as an example, including: 1% to 8%.

[0056] The antioxidant "0.3% to 1%" can be taken as a numerical range of 0.3% to 1%, and the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. For example, it includes but is not limited to: 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; or a range consisting of any two of these values, as an example, including: 0.3% to 0.8%.

[0057] The light absorber "0.3% to 2%" can take a numerical range of 0.3% to 2%, and the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. For example, it includes but is not limited to: 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%; or a range consisting of any two of these values, as an example, including: 0.3% to 1.5%.

[0058] In some embodiments, the composite material includes the following components by weight:

[0059]

[0060] Furthermore, when the distribution ratio of the control group is within the preferred range, the composite material has better high impact resistance, antistatic performance, UV resistance, flame retardancy, environmental protection and low odor performance.

[0061] In some of the embodiments, the weight ratio of polycarbonate to acrylonitrile-styrene-acrylate copolymer is (2-5):1, and the weight ratio of the polycarbonate to the compound flame retardant is (5-8):1.

[0062] It can be understood that the weight ratio of polycarbonate to acrylonitrile-styrene-acrylate copolymer can be 0.45:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:114:1 or 15:1; the weight ratio of polycarbonate to the compound flame retardant can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 and 10:1.

[0063] By further controlling the composition ratio within the preferred range, the composite material has better high impact resistance, antistatic performance, UV resistance, flame retardancy, environmental protection and low odor performance.

[0064] In a specific example, the weight ratio of the polycarbonate to the acrylonitrile-styrene-acrylate copolymer is 3.1:1, and the weight ratio of the polycarbonate to the compound flame retardant is 7.5:1.

[0065] In some embodiments, the polycarbonate comprises bisphenol A aromatic polycarbonate.

[0066] In some embodiments, the weight average molecular weight of the polycarbonate is 20000 g / mol to 30000 g / mol.

[0067] In some of the embodiments, based on the weight of the acrylonitrile-styrene-acrylate copolymer, the mass content of the acrylate structural unit is 35% to 85%.

[0068] In some embodiments, the compatibilizer includes styrene-N-phenylmaleimide-maleic anhydride copolymer.

[0069] In some embodiments, the toughening agent includes methyl methacrylate-butadiene-styrene copolymer.

[0070] In some embodiments, the composite flame retardant comprises magnesium hydroxide, zinc borate and an organophosphorus flame retardant.

[0071] Optionally, the mass ratio of the magnesium hydroxide, the zinc borate and the organophosphorus flame retardant in the compound flame retardant is (1.5-2.5):(2.5-3.5):(4.5-5.5). Furthermore, the mass ratio of the magnesium hydroxide, the zinc borate and the organophosphorus flame retardant in the compound flame retardant can be, for example but not limited to, 2:3:5.

[0072] In some embodiments, the polymer antistatic agent includes at least one of polyetheresteramide, polyetheramide and polyetherester.

[0073] In some embodiments, the antioxidant includes at least one of a hindered phenol antioxidant and a phosphate antioxidant.

[0074] In some embodiments, the light absorber includes a benzotriazole light absorber.

[0075] An embodiment of the present application provides a method for preparing a composite material. The preparation method comprises the following steps:

[0076] The components of any of the above composite materials are mixed and extruded.

[0077] In some of the embodiments, dried polycarbonate, acrylonitrile-styrene-acrylate graft copolymer ASA, compatibilizer, toughening agent, polymer antistatic agent, compound flame retardant, antioxidant and light absorber are mixed uniformly in proportion by weight and passed through the main barrel of a twin-screw extruder (screw diameter 35 mm, aspect ratio L / D=36). The temperature of the main barrel is controlled in nine sections. The temperatures from the feeding port to the die outlet are set in sequence as: 200°C, 230°C, 255°C, 255°C, 255°C, 255°C, 255°C, 255°C, 240°C.

[0078] Furthermore, the twin-screw speed is 300 rpm, and the extruded material strips are cooled in a water tank and then pelletized to obtain the product.

[0079] In addition, the composite material obtained by this preparation method also has high fluidity, which is more conducive to injection molding. Moreover, the preparation method of the composite material is simple, the processing is convenient, and it can be widely used in the preparation of automotive interior parts.

[0080] In one embodiment of the present application, there is provided a use of any of the above-mentioned composite materials in the preparation of decorative products.

[0081] In one embodiment of the present application, a decorative product is provided, which includes any of the composite materials described above.

[0082] In some embodiments, the decorative article comprises an automobile interior decoration part.

[0083] In some specific examples, the above-mentioned automobile interior decoration parts may be air-conditioning panels, automobile dashboards and other parts.

[0084] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

[0085] In order to better illustrate the present application, the contents of the present application are further described below in conjunction with embodiments.

[0086] Selection of compound flame retardants

[0087] 1. Preparation of compound flame retardant

[0088] Magnesium hydroxide, anhydrous zinc borate and an organic phosphorus flame retardant were weighed according to the mass ratio in Table 2, mixed and stirred evenly to obtain a composite flame retardant.

[0089] Table 2

[0090] Compound flame retardant 1 Compound flame retardant 2 Compound flame retardant 3 Compound flame retardant 4 Magnesium hydroxide 33 60 20 20 Zinc borate 50 30 30 70 Organophosphorus flame retardants 17 10 50 10

[0091] 2. Determination of compound flame retardant formula

[0092] According to the mass fraction, the following raw materials are provided: polycarbonate PC: 60%; ASA: 29.5%; SMI: 5%; MBS: 5%; the above-mentioned compound flame retardant: 5%; antioxidant 1010: 0.2%; antioxidant 619F: 0.3%. Among them, polycarbonate PC: bisphenol A resin with a molecular weight of 25,000 to 35,000, produced by Samsung Petrochemical Company of South Korea; ASA: acrylic rubber percentage content of about 45%, produced by Mitsubishi Rayon Company of Japan, W-450A; compatibilizer: styrene-N-phenylmaleimide-maleic anhydride copolymer (SMI): Japan Electric Chemical, MS-NA. Toughening agent: methyl methacrylate / butadiene / styrene copolymer (MBS), commercially available. Antioxidant 1010: hindered phenol antioxidant, commercially available. Antioxidant 619F: phosphate antioxidant, commercially available. Magnesium hydroxide: industrial grade, commercially available. Zinc borate: anhydrous zinc borate, industrial grade, commercially available. Organic phosphorus flame retardant: ammonium polyphosphate APP and BDP are compounded and granulated, commercially available.

[0093] The dried raw materials for preparing the above-mentioned composite materials are mixed uniformly according to the weight proportions in Table 3 and passed through the main barrel of a twin-screw extruder (screw diameter 35 mm, aspect ratio L / D=36). The main barrel is divided into nine sections to control the temperature (from the feeding port to the die outlet) of 200°C, 230°C, 255°C, 255°C, 255°C, 255°C, 255°C, 255°C, 240°C, and the twin screw speed is 300 rpm. The extruded material strips are cooled in a water trough and then pelletized to obtain a composite material.

[0094] Table 3

[0095] composition Example 1 Example 2 Example 3 Example 4 Example 5 PC 60 60 60 60 60 ASA 29.5 29.5 29.5 29.5 29.5 SMI 5 5 5 5 5 MBS 5 5 5 5 5 Compound flame retardant 1 5 / / / / Compound flame retardant 2 / 5 / / / Compound flame retardant 3 / / 5 / / Compound flame retardant 4 / / / 5 / Antioxidant 1010 0.2 0.2 0.2 0.2 0.2 Antioxidant 619F 0.3 03 0.3 0.3 0.3 <![CDATA[Charpy notched impact strength, KJ / m 2 > 62.1 48.2 56.4 49.3 51.4 Limiting oxygen index LOI (%) 24 24.3 26.5 24.7 24.2 Smoke Density Rating SDR 73.1 712 60.8 74.5 88.1 Total carbon (μgC / g) 45.3 23.5 17.8 24.5 43.3

[0096] Product performance test method:

[0097] 1. Sample preparation: The products prepared in Examples 1 to 5 were dried in a blast oven at 95°C for 5 hours, and then injection molded into standard specimens and standard plain plates (150*100*3.2mm) using a plastic injection molding machine at an injection molding temperature of 240°C. The molded specimens and plain plates were immediately placed in a glass desiccator and left at room temperature for at least 24 hours before testing.

[0098] 2. Charpy notched impact strength: tested according to IS0179-1 method, sample specifications: 80*10*4mm.

[0099] 3. Limiting oxygen index LOI: Tested according to GB / T2406.2 standard, sample specifications: 4 mm thickness, oxygen index ≥ 24 is qualified.

[0100] 4. Smoke density level SDR: Tested according to GB / T8627 standard, sample specifications: 25×25×3.2 mm, test smoke conditions: propane gas, gas pressure 276 kPa, smoke density level SDR≤70 is qualified.

[0101] 5. Total carbon VOC test: Tested according to VDA277, the test value ≤50μgC / g is qualified.

[0102] From the above table 3 examples 1 to 5, it can be seen that the flame retardant and environmentally friendly PC / ABS with the addition of compound flame retardant 3 has good mechanical properties and can meet the requirements of the new national standard for smoke density and oxygen index, and the total carbon content is less than 50 μgC / g, reaching 17.8. Therefore, compound flame retardant 3 is used in the following examples and comparative examples.

[0103] Example 1

[0104] According to the mass fraction, the following raw materials are provided: polycarbonate PC: 60%; ASA: 24.5%; SMI: 5%; MBS: 5%; the above-mentioned compound flame retardant 3: 5%; antioxidant 1010: 0.2%; antioxidant 619F: 0.3%; polymer antistatic agent NC6321: 5%; UV5411: 0.5%. UV 5411: benzotriazole light absorber, Cytec, USA. Antistatic agent: polyether ester amide type polymer antistatic agent, Sanyo, Japan, Pelestat NC6321.

[0105] The dried raw materials for preparing the above-mentioned composite materials are mixed uniformly according to the weight proportions in Table 4 and passed through the main barrel of a twin-screw extruder (screw diameter 35 mm, aspect ratio L / D=36). The main barrel is divided into nine sections to control the temperature (from the feeding port to the die outlet) of 200°C, 230°C, 255°C, 255°C, 255°C, 255°C, 255°C, 255°C, and 240°C. The twin screw speed is 300 rpm. The extruded material strips are cooled in a water trough and then pelletized to obtain a composite material.

[0106] Except for the differences in the raw materials for preparation as shown in Table 4, other conditions of Examples 2 to 5 and Comparative Examples 1 to 2 are the same (the preparation process parameters are the same).

[0107] Table 4

[0108]

[0109] Product performance test method:

[0110] 1. Sample preparation: The products prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were dried in a blast oven at 95°C for 5 hours, and then injection molded into standard specimens and standard plain plates (150*100*3.2 mm) using a plastic injection molding machine at an injection molding temperature of 240°C. The injection molded specimens and plain plates were immediately placed in a glass desiccator and left at room temperature for at least 24 hours before testing.

[0111] 2. Charpy notched impact strength: according to ISO 179-1 method, sample size: 80*10*4mm.

[0112] 3. Surface resistance: According to IEC 60093 method, use a sample with a diameter of 80 mm and a thickness of 3 mm.

[0113] 4. Xenon lamp accelerated aging: According to SAE J2412 standard, energy value: 600KJ / m 2 , measure the color difference ΔE value.

[0114] 5. Limiting oxygen index LOI: tested according to GB / T2406.2 standard, 4 mm thick specimen.

[0115] 6. Smoke density level SDR: Tested according to GB / T 8627 standard, 25×25×3.2 mm sample, propane gas, gas pressure 276 kPa.

[0116] 7.Total carbon VOC test: According to VDA277: the test value ≤50μgC / g is qualified.

[0117] From the performance test results of the above comparative examples and embodiments, it can be seen that Examples 1 to 5 obtained by adding the compound flame retardant 3 all achieved ideal notched impact, and the limiting oxygen index and smoke density level could also meet the requirements of the new national standard. The surface resistance of the plastic product was below 1012Ω, that is, it had certain antistatic properties), and the total carbon content was less than 50μgC / g, all below 25μgC / g. The above embodiments can achieve excellent mechanical properties, excellent antistatic weather resistance, and strict new national standard environmental protection requirements.

[0118] The present application aims to invent a composite material with good antistatic properties, excellent mechanical properties, UV resistance, oxygen index ≥ 24, smoke density level SDR ≤ 70, low emission and other advantages, which can be used to manufacture automotive interior parts such as automotive dashboards and air conditioning panels.

[0119] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above-described embodiments only express several implementation methods of the present application, and the description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the patent application. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several deformations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent application of this application shall be based on the attached claims.

Claims

1. A composite material, characterized in that: The composite material comprises the following components by mass percentage: The weight ratio of the polycarbonate to the acrylonitrile-styrene-acrylate copolymer is (0.45-15):1, and the weight ratio of the polycarbonate to the compound flame retardant is (3-10):

1.

2. The composite material according to claim 1, characterized in that The composite material comprises the following components by mass percentage:

3. The composite material according to claim 1, characterized in that The weight ratio of the polycarbonate to the acrylonitrile-styrene-acrylate copolymer is (2-5):1, and the weight ratio of the polycarbonate to the compound flame retardant is (5-8):

1.

4. The composite material according to any one of claims 1 to 3, characterized in that: The polycarbonate satisfies at least one of the following characteristics: (1) The polycarbonate comprises bisphenol A type aromatic polycarbonate; (2) The weight average molecular weight of the polycarbonate is 20000 g / mol to 30000 g / mol.

5. The composite material according to any one of claims 1 to 3, characterized in that: The composite material satisfies at least one of the following characteristics: (1) Based on the weight of the acrylonitrile-styrene-acrylate copolymer, the mass content of the acrylate structural unit is 35% to 85%; (2) The compatibilizer includes styrene-N-phenylmaleimide-maleic anhydride copolymer; (3) The toughening agent includes methyl methacrylate-butadiene-styrene copolymer.

6. The composite material according to any one of claims 1 to 3, characterized in that: The composite flame retardant comprises magnesium hydroxide, zinc borate and an organic phosphorus flame retardant; Optionally, the mass ratio of the magnesium hydroxide, the zinc borate and the organophosphorus flame retardant in the composite flame retardant is (1.5-2.5):(2.5-3.5):(4.5-5.5).

7. The composite material according to any one of claims 1 to 3, characterized in that: The composite material satisfies at least one of the following characteristics: (1) The polymer antistatic agent comprises at least one of polyetheresteramide, polyetheramide and polyetherester; (2) the antioxidant comprises at least one of a hindered phenol antioxidant and a phosphate antioxidant; (3) The light absorber includes a benzotriazole light absorber.

8. A method for preparing a composite material, characterized in that: The steps include: The components of the composite material according to any one of claims 1 to 7 are mixed and extruded.

9. Use of the composite material according to any one of claims 1 to 7 in the preparation of decorative products.

10. A decorative product, characterized in that: The decorative article comprises the composite material according to any one of claims 1 to 7; Optionally, the decorative article comprises an automotive interior trim part.